Design of a control with multiple inputs multiple outputs by decoupling (2021)
In industry, most processes can be modeled by a system of equations that can be monovariable or multivariable. In our case, we will present a multivariable system more adjusted to real cases and on which a control system is available. This article presents a decoupling control method for two inputs two outputs through a centralized multivariable controller using a decoupling network and a diagonal controller, this technical advantage allows reduction in computing time. It shows the methodology by which a multivariate system can be represented as the composition of different coupled systems in this way that the control of the variables involved in it can be done separately, facilitating the control system, this implies a modification in the outputs to be affected. In the same way, the two-inlet with 2-outlet distillation system was also studied. © Published under licence by IOP Publishing Ltd.